Sprint training enhances ionic regulation during intense exercise in men - McKennan, M. J.; Heigenhauser, G. J. F.; McKelvie, R. S.; MacDougall, J. D.; Jones, N. L. (The Journal of Physiology, 1997)
Sprint training increased the capacity for muscular work and improved muscle strong ion regulation during exercise. Increased muscle Na+ and K+ uptake during exercise after training are consistent with a greater activation of the muscle Na+-K+ pump, reduced cellular K+ loss and the observed reduced rate of fatigue. There was little evidence of enhanced glycolysis after training, suggesting that the major energetic adaptation after sprint training was enhanced aerobic metabolism. A consequence of the improved muscle strong ion regulation was a lower arterial plasma [SID] due to lower plasma [K+] and [Na+], and higher plasma [Lac-], resulting in a greater plasma acidosis. Thus, sprint training improved muscle ion regulation, associated with increased intense exercise performance, at the expense of a greater systemic acidosis.